Modified Newton's Law of Gravitation due to Minimal Length in Quantum Gravity - Ahmed Farag Ali; A. Tawfik (Advances in High Energy Physics)
A recent theory about the origin of the gravity suggests that the gravity is originally an entropic force. In this work, we discuss the effects of generalized uncertainty principle (GUP) which is proposed by some approaches to quantum gravity such as string theory, black hole physics, and doubly special relativity theories (DSR), on the area law of the entropy. This leads to a